Early Endoscopy Can Shorten the Duration of Hospitalization in Suspected Variceal Hemorrhage. (24th July 2013) - Guan, Hong-Lin; Lin, Hsin-Yi; Lee, Yi-Kung; Hsu, Chen-Yang; Su, Yung-Cheng
Abstract : Background . Endoscopic treatment in patients with acute variceal hemorrhage should be performed within 12 hours, but the recommendation is based on the experts' opinion. Objective . Our study investigated if time to endoscopy was a significant factor that could alter the outcomes of patients with suspected variceal hemorrhage. The primary outcome was the length of hospital stay and the mortality. The secondary outcomes were complications during observation periods. Methods . Patients were included if variceal hemorrhage was suspected in the emergency department. Patients were further divided into early (receiving endoscopy within 12 hours) and delayed groups (receiving endoscopy after 12 hours), and each patient was matched using a standard propensity score greedy-matching algorithm. The primary and secondary outcomes were compared accordingly. Results . 1442 patients met our inclusion criteria and therefore were enrolled for further analysis. In the Cox regression model, log time to endoscopy was not a significant factor. In the propensity score assignment, 566 patients (283 in each group) were further selected into the subcohort ( P value = 0.8001). Kaplan-Meier curves showed a discharge benefit favoring the early endoscopy over the control group. The mortality rates and complications were not statistically different between the two groups ( P value = 0.0045). Conclusion . Early endoscopy before 12 hours in patients with suspected variceal hemorrhage could result in shorter length of hospitalization without increasing the mortalities and complications. The results would help emergency physicians in decisions making when these patients are encountered.